Development and characterization of polymorphic microsatellite markers in Rhododendron simsii (Ericaceae). Issue 1 (22nd January 2016) - Wang, Shuzhen; Li, Zhiliang; Jin, Weibin; Xiang, Fu; Xiang, Jun; Fang, Yuanping
Abstract: A set of 14 polymorphic microsatellite markers has been developed and characterized using FIASCO (fast isolation by AFLP of sequences containing repeats) methods for the garden plant, R hododendron simsii Planch. Forty‐one R . simsii individuals showing large morphological differences were used to identify these markers. The total number of alleles for each locus ranged from 2 to 6, with an average value of 3.643. The expected heterozygosities and observed heterozygosities ranged from 0.137 to 0.778 and 0.000 to 0.769, respectively. Eight loci exhibited significant deviations from Hardy‐Weinberg equilibrium. Among these microsatellites, seven could successfully be transferred to four related species ( R . pulchrum, R . hybrida, R . alutaceum and R . molle (Blume) G. Don). These novel microsatellite markers could be further used for assessment of genetic diversity and population structure, phylogeographic analysis and marker‐assisted selection for R . simsii and other Rhododendron species. Abstract : A set of 14 polymorphic microsatellite markers have been developed from Rhododendron simsii. Seven microsatellites could successfully cross‐species amplify in four related species.